(untitled) (Bangladesh Journal of Medical Science, 2026)
Background The pancreas is a double-entity organ, and previous studies have shown that a significant proportion of patients with diabetes mellitus and obesity have pancreatic exocrine insufficiency (PEI). Increased risks of metabolic disorders, metabolic syndrome, and diabetes were linked to low serum amylase levels. Methodology Study population was be taken from patients visiting to K.R Hospital, Mysore with type-2 diabetes mellitus for follow up and they are grouped into two, based on their BMI as obese diabetics & non-obese Diabetics. Result The present study showed statistically decreased Serum Amylase in obese diabetics when compared with non-obese type 2 diabetic and increased Total Cholesterol/ HDL ratio. Present study also shows increased serum Triglyceride, Total cholesterol, LDL, VLDL in obese diabetic when compared with nonobese type 2 diabetes but not statistically significant. The study showed negative correlation between Serum Amylase with blood glucose & serum HDL but not statistically significant. Conclusion The current study findings suggest that lower serum amylase levels in obese people with type 2 diabetes may be linked to an exocrine-endocrine axis disruption, which impairs exocrine pancreatic function. This could then be utilized as a potential marker to evaluate the exocrine functions of the pancreas. BJMS, Vol. 25 No. 01 January’26 Page : 125-135